Conservação ex situ de Hancornia speciosa Gomes: o banco ativo de germoplasma da Embrapa Tabuleiros Costeiros - Oliveira, Jéssica Monalisa Santos Pereira (2018)
Hancornia speciosa Gomes is a tropical species that is native to Brazil. It is exploited in many different extractive ways. Due to the socioeconomic and cultural importance of the species, the families of traditional communities in its areas of occurrence have their income based on the collection of its fruits at the time of their fruiting. At the same time – while noticing the great decrease in areas of natural occurrence, these present times have become worrying conditions for the future germination of the species and its conservational development in Embrapa’s Mangrove Germplasm Bank situated in the Coastal Tablelands of Sergipe. The present work was developed with the objective of evaluating the enrichment, the development and the characterization of the accessions that comprise this Germplasm Bank. We used 32 descriptors in order to evaluate 299 individuals, which represented the 27 accessions. There was a great variety of differences among them, as far as their plant morphology, their biometrics and their fruit qualification attributes were concerned. The results were published in the Bioversity International journal and they were used for the elaboration of conservation strategies for the Germplasm Bank, together with its future direction of research on the genetics of breeding.